2019
DOI: 10.2196/14645
|View full text |Cite
|
Sign up to set email alerts
|

User Engagement and Attrition in an App-Based Physical Activity Intervention: Secondary Analysis of a Randomized Controlled Trial

Abstract: BackgroundThe success of a mobile phone app in changing health behavior is thought to be contingent on engagement, commonly operationalized as frequency of use.ObjectiveThis subgroup analysis of the 2 intervention arms from a 3-group randomized controlled trial aimed to examine user engagement with a 100-day physical activity intervention delivered via an app. Rates of engagement, associations between user characteristics and engagement, and whether engagement was related to intervention efficacy were examined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 67 publications
4
149
0
2
Order By: Relevance
“…Regardless, 2 analyses (mixed factorial ANOVAs and correlational analyses) were conducted to determine if there was a dose effect of app usage on the outcome measures. The results of these analyses did not indicate that there was a dose effect and the very low correlations support this notion despite the fact that other exercise and smartphone app studies have linked exercise exposure to efficacy [ 51 ]. Further investigation into the dosing of the 9zest app-guided exercise using a more rigorously controlled design is warranted.…”
Section: Discussionmentioning
confidence: 90%
“…Regardless, 2 analyses (mixed factorial ANOVAs and correlational analyses) were conducted to determine if there was a dose effect of app usage on the outcome measures. The results of these analyses did not indicate that there was a dose effect and the very low correlations support this notion despite the fact that other exercise and smartphone app studies have linked exercise exposure to efficacy [ 51 ]. Further investigation into the dosing of the 9zest app-guided exercise using a more rigorously controlled design is warranted.…”
Section: Discussionmentioning
confidence: 90%
“…Despite these advantages, persistent usage of online-based interventions is a concern ( Eysenbach, 2005 ). Previous studies have reported that usage of online-based interventions dropped under 50% within one to two month after starting the program ( Geraghty et al, 2013 ; Edney et al, 2019 ; Wangberg et al, 2008 ). Low intervention usage may not necessarily mean that participants have not improved their target behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The study characteristics are summarized in Multimedia Appendix 2 . Of the 24 studies, 17 used an RCT design [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], 4 used a retrospective analysis [33][34][35][36], and 3 used a single-group pre-and posttest quasi-experimental design [37][38][39]. Although 20 studies used an RCT or single-group preand-posttest quasi-experimental design, it was the correlational studies nested within these larger parent studies that were of interest for this review.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 17 RCT studies, 14 conducted an a priori power analysis. Of these 14 RCTs, 3 detected a significant difference in the primary outcome between groups [21,23,27], 9 did not detect a significant difference in the primary outcome between groups [16,17,22,[24][25][26]29,31,32], and 2 did not report the results of the difference in the primary outcome between groups [18,30]. One of the studies that did not detect a significant difference between groups did not achieve the target sample size [32].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation